The Life and Times of Aboutness: A Review of the Library and Information Science Literature - Rondeau, Sophie (Evidence Based Library and Information Practice, 2014)
Objective – This paper explores the concept of “aboutness”, its related terms, and the process of aboutness determination as found in the Library and Information Science Literature. Methods – A review of the literature pertaining to aboutness determination and related terms specific to Library and Information Science was undertaken, borrowing extensively from the literature review of Daniel Joudrey’s (2005) dissertation, Building puzzles and growing pearls: A qualitative exploration of determining aboutness, as well as examining a small selection of research and articles not discussed by Joudrey. In addition, a concept map was developed to outline many of the concepts and theories found. Results – The LIS literature demonstrates conflicting positions surrounding the term aboutness and its correlates. Despite the lack of firm agreement on terminologies, the notion of subject is explored because it featured prominently in the literature. As well, intensional and extensional aboutness are explored in contrast to a more subjectivist perspective which asserts that a document's aboutness cannot be separated from its reader. Aboutness determination is also examined through the lens of theme and rheme, that is what is presupposed in a document versus what is new. Aboutness from the user perspective featured considerably in the literature, with many authors asserting both the importance and the challenge of mediating knowledge on behalf of the user. The stage of aboutness determination in the complete process of subject indexing is also presented here, and the findings demonstrate that the stages are anything but linear and sequential. Conclusion – While the findings are more expositional than conclusive, they demonstrate the complexities and challenges surrounding the concept of “aboutness” and the process of its determination. The value of this review is in its ability to present the ways in which scholars and practitioners have attempted to grapple with this conundrum. Although indexers may find temporary solace in cataloguing manuals that outline aboutness determination procedures, underneath these “safe surfaces” is an ambiguous concept further complicated by obscure and incomplete processes. This review provides an opportunity to reflect on those challenges and to further the discussion.